Neuropathic Pain in Taxane-Induced Peripheral Neuropathy: Evidence for Exercise in Treatment. (October 2019) - Andersen Hammond, Elizabeth; Pitz, Marshall; Shay, Barbara
One in 2 Canadians is expected to acquire cancer in their lifetime. Many cancers, including breast, ovarian, and lung cancer, are treated using taxane chemotherapy with curative intent. A major adverse effect with the use of taxane chemotherapeutic agents is taxane-induced peripheral neuropathy (TIPN). Both positive (spontaneous pain, heightened sensitivity with light touch, tingling, itching, burning) and negative (loss of touch, loss of hot/cold sensations, and loss of pain) sensory symptoms can be experienced in the hands and feet and worsen with increasing dose and treatment duration. The pathophysiology of TIPN is still unknown but likely involves multiple mechanisms, including microtubule impairment, neuroimmune and inflammatory changes, ion channel remodeling, impaired mitochondrial function, and genetic predisposition. This review highlights current theories on the pathophysiology for TIPN, the cellular responses thought to maintain neuropathic pain, and the growing support for exercise in the treatment and prevention of peripheral neuropathy and neuropathic pain in both animal and human models.